Identification of amino acid residues of a designed ankyrin repeat protein potentially involved in intermolecular interactions with CD4: Analysis by molecular dynamics simulations - Nimmanpipug P. (2014)
We applied molecular dynamics simulations to investigate the binding properties of a designed ankyrin repeat protein, the DARPin-CD4 complex. DARPin 23.2 has been reported to disturb the human immunodeficiency virus (HIV) viral entry process by Schweizer et al. The protein docking simulation was analysed by comparing the specific ankyrin binder (DARPin 23.2) to an irrelevant control (2JAB) in forming a composite with CD4. To determine the binding free energy of both ankyrins, the MM/PBSA and MM/GBSA protocols were used. The free energy decomposition of both complexes were analysed to explore the role of certain amino acid residues in complex configuration. Interestingly, the molecular docking analysis of DARPin 23.2 revealed a similar CD4 interaction regarding the gp120 theoretical anchoring motif. In contrast, the binding of control ankyrin to CD4 occurred at a different location. This observation suggests that there is an advantage to the molecular modification of DARPin 23.2, an enhanced affinity for CD4. © 2011 Elsevier Inc. All rights reserved.